(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
Infection control education and training are paramount in ensuring the safety of both healthcare workers and patients. This article explores the significance of comprehensive education and training programs in promoting compliance and competency among healthcare professionals. It discusses the key components of effective infection control training, challenges in implementation, and strategies to enhance engagement and knowledge retention. By emphasizing the importance of continuous education and fostering a culture of infection prevention, healthcare institutions can significantly reduce the risk of healthcare-associated infections and promote better patient outcomes.